Respostas

2013-12-15T00:24:36-02:00
{x+2y=23 (*-2)
{2x-5y=1

-2x - 4y = -46
2x   -5y = 1
-9y = -45
9y = 45
y = 45/9
y = 5

2x - 5*5 = 1
2x -25 = 1
2x = 1+25
2x = 26
x = 26/2
x = 13

s={5,13}
1 1 1
2013-12-15T00:39:26-02:00
Primeiro encontramos x.
x = 23 - 2y
segundo substituimos x na segunda equação 2x - 5y = 1
2.( 23 - 2y ) - 5y = 1
46 - 4y - 5y = 1
- 9y + 46 = 1
-9y = 1 - 46
- 9y = - 45 .( -1 )
9y = 45
y = 45/9
y = 5
Vamos encontar x.
x = 23 - 2.5
x = 23 - 10
x = 13
vc errou ,na parte da divisão de y = 45/9 5
= 5 e não 45